Ethnobotanical assessment of medicinal plants used in alpine regions of Uttarakhand, west Himalaya - Thapliyal, Neha; Bhojak, Puja; Arya, Dhani; Sekar, K. Chandra (Ethnobotany Research and Applications, 2024)
Background: Himalaya, the youngest mountain biodiversity hotspot, embraces a variety of high-value medicinal flora used by the indigenous population to treat various health related ailments. However, this indigenous knowledge is gradually being lost owing to generation gaps and dependency on modern medicine. Thus, documentation of indigenous knowledge and evaluation of the use of plants assume greater significance to preserve the socio-economic and cultural heritage of mountain communities. Methods: The study was conducted during the months of July-October in 2019-2022 in different alpine regions of Uttarakhand and ethnopharmacological data was collected through questionnaire-based interviews and discussions with local people. The Use Value (UV) and Fidelity Level (FL) for each documented species was calculated along with informant consensus factor (ICF) to estimate the relative importance of species. Rapid Threat Assessment (RTA) was conducted using 10 criteria to identify the priority medicinal plants. Results: A total of 77 plant species in 69 genera and 30 families were documented to have variety of roles in treating 44 different kinds of ailments by the locals. The highest species were used for dermatological (cuts and wounds, boils, blisters) and gastrointestinal (stomachache, indigestion, dysentery, diarrhea) problems. Roots/rhizomes and leaves were most utilized in making herbal formulations, and method of administration of 37 species was oral, 29 species was topical and 11 species were taken both orally and topically. Aconitum heterophyllum, Nardostachys jatamansi and Picrorhiza kurroa and were the most valuable species in terms of use value (>0.90) and frequency of citation (>0.50). The ICF values for all ailment categories ranged from 0.73 to 0.94, indicating a high level of informant agreement, with highest for urogenital and gastrointestinal disorders. RTA scores for N. jatamansi (31) and P. kurroa (32) identified them to be highly threatened medicinal plants in the region. Some other vulnerable medicinal plants include A. heterophyllum, Angelica glauca, Malaxis muscifera, Podophyllum hexandrum and Rheum australe. Conclusions: The study provides comprehensive information about the traditional knowledge of herbal medicine as well as identified priority species at high-risk of extinction, which will pave way towards initiating conservation, sustainable harvesting and enhancing cultivation practices of medicinal plants in Himalaya. Keywords: Ethnomedicine, medicinal plants, alpine regions, traditional knowledge, threat assessment, Himalaya